Thickness Dependence of Ice Removal Stress for a Polydimethylsiloxane Nanocomposite: Sylgard 184 - Wang, Chenyu; Fuller, Trae; Zhang, Wei; Wynne, Kenneth J (Langmuir, 2014)
Minimizing adhesion of ice has been the subject of extensive studies because of importance to applications such aircraft wings, spacecraft, and power transmission wires. A growing interest concerns coatings for wind turbine blades and refrigeration. Herein, a new laboratory test was employed to obtain the thickness dependence of ice adhesion for Sylgard 184a filled polydimethylsiloxane elastomer. A correlation between ice adhesion and coating thickness (t) was found that follows a relationship developed by Kendall over 40 years ago for removal of a rigid object from an elastomer. With a 0.05 mm/s probe speed a nearly linear relationship between peak removal stress (P s) and 1/t 1/2 was obtained with P s ∼ 460 kPa for an 18 μm coating, decreasing to ∼120 kPa for 533 μm. Preliminary results suggest that below ∼10 μm P s departs from the 1/t 1/2 correlation while above ∼500 μm a limiting value for P s may be reached. We previously reported that probe speed has negligible effect on the glassy polymer PMMA. In contrast, probe speed is identified as an important variable for testing ice release on elastomeric Sylgard 184 coatings. While work of adhesion, which is related to surface free energy, is recognized as an important factor that can affect ice release, the results reported herein show that coating thickness can override this single parameter for elastomeric substrates.